2013
DOI: 10.1002/jca.21293
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte‐exchange with the OPTIA™ cell separator in patients with sickle‐cell disease

Abstract: Erythrocyte-exchange (EEX) has proven to be a very useful tool in sickle-cell disease (SCD) patients either during acute painful crisis unresponsive to hydration and/or analgesia or as a prophylactic treatment in high risk patients in those who do not tolerate hydroxyurea (HU), with the aim of lowering HbS levels. EEX may be performed either by using continuous- or discontinuous flow devices, the former being of choice in children or in low-weight patients. Thus, a low extracorporeal blood volume (EBV) could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Our results are consistent with those recently reported by Perseghin and colleagues . These authors compared RBCX procedures performed with the SO to those performed with the precedent, CS, device.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with those recently reported by Perseghin and colleagues . These authors compared RBCX procedures performed with the SO to those performed with the precedent, CS, device.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those recently reported by Perseghin and colleagues. 22 These authors compared RBCX procedures performed with the SO to those performed with the precedent, CS, device. They found that the two devices were comparable in achieving the programmed target postprocedure Hct and that the lower extracorporeal volume of the SO, 185 mL compared with 270 mL for the CS, allowed RBCX procedures to be done on low-weight patients without the need for preliminary priming of the circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the performances of the SO device when using the RBCX technique associated (SO/DE) or not (SO) with the depletion step for patients with SCA. [13][14][15][16][17][18] These studies showed similar performance of SO compared to CSP both associated and not associated with DE. However, the number of RBCPs saved when using SO/DE has not been accurately evaluated since previous studies focused mainly on the performance and safety of the SO/DE technique.…”
mentioning
confidence: 66%
“…Several studies have described the performances of the SO device when using the RBCX technique associated (SO/DE) or not (SO) with the depletion step for patients with SCA . These studies showed similar performance of SO compared to CSP both associated and not associated with DE.…”
mentioning
confidence: 99%
“…A new apheresis system, the Spectra Optia (Terumo BCT, Lakewood, CO) has been recently introduced in the clinical setting. So far, studies about this new apheresis device report on mononuclear cell collection, on plasma‐exchange procedures, and on RBC exchange, respectively …”
mentioning
confidence: 99%